Early Life Stress Predicts Depressive Symptoms in Adolescents During the COVID-19 Pandemic: The Mediating Role of Perceived Stress - Gotlib, Ian H.; Borchers, Lauren R.; Chahal, Rajpreet; Gifuni, Anthony J.; Teresi, Giana I.; Ho, Tiffany C. (Frontiers in Psychology, 2021)
Background: Exposure to early life stress (ELS) is alarmingly prevalent and has been linked to the high rates of depression documented in adolescence. Researchers have theorized that ELS may increase adolescents’ vulnerability or reactivity to the effects of subsequent stressors, placing them at higher risk for developing symptoms of depression. Methods: We tested this formulation in a longitudinal study by assessing levels of stress and depression during the COVID-19 pandemic in a sample of adolescents from the San Francisco Bay Area (N=109; 43 male; ages 13-20 years) who had been characterized 3-7 years earlier (M=5.06, SD=0.86 years) with respect to exposure to ELS and symptoms of depression. Results: As expected, severity of ELS predicted levels of depressive symptoms during the pandemic (r(107)=0.26, p=.006), which were higher in females than in males (t(107)=-3.56, p<.001). Importantly, the association between ELS and depression was mediated by adolescents’ reported levels of stress, even after controlling for demographic variables. Conclusions: These findings underscore the importance of monitoring the mental health of vulnerable children and adolescents during this pandemic and targeting perceived stress and isolation in high-risk youth.